Optimalisasi Pajak dan Retribusi Melalui Pariwisata dan Ekonomi Kreatif di Balangan - Sasongko, Dhimas Wahyu; Yuliani, Rahma (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to measure the potential for regional taxes and levies through city tourism and the creative economy, analyze the potential and obstacles to the integration of city tourism and the creative economy in Balangan Regency; and measuring how much potential PAD develops from taxes and levies for the development of tourism and the creative economy in Balangan Regency. This research uses a descriptive qualitative method by focusing on the efforts made by Regional Government Organizations as well as the factors that encourage or inhibit the development of taxes and levies to increase the PAD of Balangan Regency. The analysis techniques used by researchers are data analysis before going to the field, data analysis using the Miles and Huberman model, feasibility analysis through Potential and Constraints, and data calculation analysis. The results of this research show that hotel taxes, restaurant taxes and the like, food/catering services taxes increased by 0.06%, 4.54% and 4.94% respectively and the affected levies were business services levies (recreational services, tourism and sports by 100% and use of regional assets by 8.08%) and parking services on the side of public roads by 34.97%. The potential increase in taxes and levies also affects the increase in PAD by 0.408%.